Spatio-temporal influence of physicochemical parameters on phytoplankton assemblage in coastal brackish lagoon: Gomishan Lagoon, Caspian Sea, Iran - MOHAMMAD JABBARI; MORTEZA SALAHI; RASOUL GHORBANI (Society for Indonesian Biodiversity, 2018)
Jabbari M, Salahi M, Ghorbani R. 2018. Spatio-temporal influence of physicochemical parameters on phytoplankton assemblage in coastal brackish lagoon: Gomishan Lagoon, Caspian Sea, Iran. Biodiversitas 19: 2020-2027. The objective of this study was to determine the spatiotemporal distribution pattern of phytoplankton assemblage due to physico-chemical heterogeneity in coastal brackish lagoon of Gomishan. An inter-annual cycle of sampling period (April 2014-March 2015) and spatially stratified random sampling were established to examine 24 spatiotemporal scenarios. Water samples were preserved in 1 and 0.5 liter dark Polythene bottles from each station for assessing plankton community and chlorophyll a, respectively. The applied multivariate approach including hierarchical cluster analysis for (dis)similarity test of environmental factors, principle component analysis (PCA) and canonical correspondence analysis (CCA) was used to illustrate the pattern of phytoplankton variability in relation to environmental characteristics. The results showed that mean salinity, temperature, pH, total nitrogen, phosphorus, silica, turbidity, and electrical conductivity (EC) were 22.8±5.9 (ppt), 23.4° C, 8.18, 2.49 (mg.l-1), 0.258 (mg.l-1), 3.39 (mg.l-1), 42.12 (NTU), and 3.78 (dS/m3), respectively. Scenarios S5AT, S5W, S6W, S6AT were distinguished from other scenarios with more than 90% similarity, subsequently S1SU and S5SU with about 80% similarity. Inter-annual mean density of total phytoplankton (cell.l-1) was 2.45×106, whereas in northern sector it was constant with only a peak in June, but in southern sector it was more tolerant, so in April it tended to increase with a peak (7.2×106) in July which was the maximum density over the year. The phytoplankton assemblage of the lagoon comprised 47 species from 5 different classes including Bacillariophyta, Pyrrophyta, Chlorophyta, Cyanophyta, and Euglenophyta.